Long-term efficacy and safety of infliximab plus methotrexate for the treatment of polyarticular-course juvenile rheumatoid arthritis: findings from an open-label treatment extension. Issue 4 (17th March 2010) - Ruperto, Nicolino; Lovell, Daniel J; Cuttica, Ruben; Woo, Patricia; Meiorin, Silvia; Wouters, Carine; Silverman, Earl D; Balogh, Zsolt; Henrickson, Michael; Davidson, Joyce; Foeldvari, Ivan; Imundo, Lisa; et al.
Abstract : Objective: To assess the long-term efficacy and safety of infliximab plus methotrexate in juvenile rheumatoid arthritis (JRA). Methods: Patients eligible for the open-label extension (OLE, weeks 52–204) received infliximab 3–6 mg/kg every 8 weeks plus methotrexate. Results: Of the 78/122 (64%) children entering the OLE, 42 discontinued infliximab, most commonly due to consent withdrawal (11 patients), lack of efficacy (eight patients) or patient/physician/sponsor requirement (eight patients). Infliximab (mean dose 4.4 mg/kg per infusion) was generally well tolerated. Infusion reactions occurred in 32% (25/78) of patients, with a higher incidence in patients positive for antibodies to infliximab (58%, 15/26). At week 204, the proportions of patients achieving ACR-Pedi-30/50/70/90 response criteria and inactive disease status were 44%, 40%, 33%, 24% and 13%, respectively. Conclusions: In the limited population of JRA patients remaining in the study at 4 years, infliximab was safe and effective but associated with a high patient discontinuation rate. Clinical trials registration number NCT00036374.